obspyDMT: A Python toolbox for retrieving and processing of large seismological datasets - Hosseini, K; Sigloch, K (Copernicus Publications, 2017)
We present obspyDMT, a free, open source software toolbox for the query, retrieval, processing and management of seismological data sets, including very large, heterogeneous, and/or dynamically growing ones. obspyDMT simplifies and speeds up user-interaction with data centers, in more versatile ways than existing tools. The user is shielded from the complexities of interacting with different data centers and data exchange protocols, and is provided with powerful diagnostic and plotting tools to check the retrieved data and meta-data. While primarily a productivity tool for research seismologists and observatories, easy-to-use syntax and plotting functionality also make obspyDMT an effective teaching aid. Written in the Python programming language, it can be used as a stand-alone command line tool (requiring no knowledge of Python) or can be integrated as a module with other Python codes. It facilitates data archival, pre-processing, instrument correction, and quality control – routine but non-trivial tasks that can consume much user time.We describe obspyDMT’s functionality, design and technical implementation, accompanied by an overview of its use cases. As an example of a typical problem encountered in seismogram preprocessing, we show how to check for inconsistencies in response files of two example stations. We also demonstrate the fully automated request, remote computation, and retrieval of synthetic seismograms from IRIS DMC’s Syngine webservice.